The Makkah–Madinah Transform Zone: a relic rift-to-rift continental transform formed during early Arabia–Nubia plate separation - Thamer Aldaajani; Kevin P. Furlong (Geoscience Letters, 2022)
Abstract The continental-rifting of Arabia from Nubia, and the initial evolution of the Red Sea spreading center includes many of the continental-rifting to ocean-spreading processes, in particular transform formation, and the eventual development of a mid-ocean ridge. The recent occurrence of this rifting and the multi-stage evolution of the plate boundary has preserved of key components of the early-stage plate boundary development. We find that the Makkah–Madinah Transform Zone (MMTZ) represents a rift-to-rift continental transform fault that served as a primary component of the initial plate boundary between Arabia and Nubia. It connected the more evolved southern Red Sea mid-ocean ridge to the initially dominant Sirhan Rift. During this time, the MMTZ served as a primary lithospheric-scale boundary between the Arabia and Nubia plates. The Sirhan Rift and the MMTZ connection to the Red Sea spreading center was mostly abandoned with the development of the Dead Sea fault, and localization of extension in the present-day northern Red Sea. The transition to the present tectonic setting suggests an ephemeral rift–rift–transform triple junction within the central Red Sea connecting the localized southern Red Sea rift, a developing northern Red Sea rift, and the MMTZ transform.